Development of TCM herb and chemotherapeutic drug interaction database - Yen, Sheng Xiang (2014)
In the recent decades, complementary and alternative medicine (CAM) has gained popularity worldwide. Traditional Chinese Medicine (TCM) is the most widely used CAM in the Chinese predominant population of Singapore. The concurrent usage of TCM herbs in cancer patients undergoing chemotherapy is not uncommon. However, many patients do not confide in their oncologist about their TCM usage. This gives a lot of potential for TCM herb-drug interactions, which may result in adverse effects on the health of the patients. This setting calls for a database for TCM herb-drug interactions to be made available for use by healthcare professionals to manage patients on concurrent use of TCM herbs and chemotherapeutic drugs. The purpose of this project is to create a database of evidence of interactions between TCM herbs and chemotherapeutic drugs. A systematic search for full articles containing studies of TCM herb-chemotherapeutic drug interactions was conducted. The information collected was further reviewed and compiled into a database. Constant addition of relevant information is required to build a comprehensive and clinically-relevant TCM herb-chemotherapeutic drug interactions database.